Assessing the phytosanitary threats of two non-native crickets under temperature change - Anna K. Kulessa; Ross N. Cuthbert; Ismael Soto; Paride Balzani; Mathieu Toutain; Antonín Kouba; Phillip J. Haubrock (Journal of Pest Science, 2025)
Numerous phytosanitary threats challenge global agriculture, ecosystems, and food security. These threats are exacerbated by non-native species and diseases that are projected to intensify in the future due to global warming and anthropogenic habitat alterations. Assessments of the ecological impacts of overlooked phytosanitary threats are urgently needed under shifting environments. In this study, the potential effects of two non-native Orthoptera species (the house cricket Acheta domesticus and the two-spotted cricket Gryllus bimaculatus ) were assessed using functional response analyses. We quantified their potential impacts on agriculturally relevant crops (millet) under increasing temperatures (20 °C, 25 °C, and 30 °C) as individuals and between interspecific pairs. The experiments revealed similar impacts on seeds between both species and across temperatures. Temperature tended to amplify consumption rates and functional responses. The combined interspecific cricket presence generally yielded an additive effect on seeds, with a few instances of synergistic interactions, whereby non-trophic interaction strengths significantly interacted with resource density and temperature. Both species demonstrated remarkable adaptability to varying temperatures, with low mortality accentuating their capacity for impacts under current and future temperatures. This emphasizes the imperative of including both species in phytosanitary assessments. Moreover, population monitoring and the implementation of effective management strategies emerge as pivotal measures for safeguarding agricultural productivity and conserving local ecosystems in the future. The study’s findings thus underscore the potential impact of A. domesticus and G. bimaculatus , particularly in the context of steadily ascending temperatures, to pose a risk to agricultural productivity and food security.